Resummation of threshold logarithms in deeply-virtual Compton scattering - J. Schoenleber (Journal of High Energy Physics, 2023)
Abstract I derive an all-order resummation formula for the logarithmically enhanced contributions proportional to α s n x ± ξ $$ \frac{α_s^n}{x± ξ } $$ log ξ ± x 2 ξ k $$ {\left(\frac{ξ ± x}{2ξ}\right)}^k $$ in the quark coefficient function of deeply-virtual-Compton scattering and the pion-photon transition form factor in momentum space. The resummation is performed at the next-to-next-to-leading logarithmic accuracy. The key observation is that the quark coefficient function itself factorizes in the x → ±ξ limit, which allows for a resummation using renormalization group equations. A preliminary numerical analysis suggests that the corrections due to resummation for the quark contribution might be small.